Análise dos limites máximos de inserção de geração eólica em redes de distribuição conforme a variação de tensão de regime permanente - Löwenberg, Vanessa Viquetti (2013)
This work considers the connection of wind power units to the distribution system, aiming at verifying the maximum power limits that can be connected complying with given connection requirements. The maximum power limits have been characterized in terms of maximum integration levels, to the equivalent capacity in the connection node, and in terms of maximum penetration levels, to the full load power feeder. The steady-state voltage in the distribution system nodes has to comply with a priori given maximum variation limits for all possible wind farm working conditions, supplying from 20 to 100% of its nominal power. The research has been developed in two different distribution feeders: a 5-nodes distribution feeder, connecting the wind farm at four different points and considering three different load levels; a 32-nodes distribution feeder, connecting the wind farm to ten different nodes of the system and also considering three different load levels. The maximum integration and penetration levels of wind power have been evaluated in terms of (i) the connection node characteristics (equivalent X/R ratio impedance and voltage); (ii) the feeder load; (iii) the connection node. The connection of either one or two wind farms has been considered for both feeders, assuming wind farms with equal characteristics. The analysis showed strong inﬂuence of the impedance X/R ratio on the maximum wind energy integration and penetration levels. The feeder load inﬂuences these levels in a non-linear manner and in some cases also an in inverse way, i.e. the load increasing can either increase or decrease the maximum integration level. The equivalent voltage inﬂuence on the maximum wind power integration and penetration was not evident in the performed tests. The feeder structure did inﬂuence the levels since, in many cases, the maximum integration and penetration levels of wind power have not been determined by the voltage in the connection node but by the voltage in other feeder s node. In general, the connection of two wind farms showed higher wind energy penetration levels compared to only one wind farm, being more or less expressive according to the connecting node characteristics.